Developing Marketing Strategies for Student Entrepreneurship Products at SMA Negeri 1 Karo to Improve Economic Independence and Business Skills - Jamaluddin Jamaluddin; Lenta Friska Purba; Dede Ansyari Guci; Renny Lubis; Susan Novrini (Abdimas Paspama, 2025)
This community service program aims to develop effective marketing strategies for students' entrepreneurial products at SMA Negeri 1 Karo, with the goal of increasing their economic independence and entrepreneurial skills. This activity includes mentoring and assisting students in identifying potential markets for their products, as well as providing training in practical marketing techniques, including branding, social media promotion, and sales strategies. With an emphasis on developing marketing knowledge and entrepreneurial skills, this initiative is designed to empower students to manage and develop their own businesses, ultimately supporting their personal growth and future career opportunities. The program is expected to not only enhance students' business insights but also foster an entrepreneurial spirit and independence, preparing them to face the challenges of the modern economic landscape.